Health related quality of life of tuberculosis patients in South India: A longitudinal assessment study. - Vasantha Mahalingam; Muniyandi Malaisamy; Bella Devaleenal Daniel; Adhin Bhaskar; Lavanya Jayabal; Lakshmi Murali; Bharadhidasan Palani; Kavi Mathiyazhagan; Sai Madhu Yadla; Padmanaban Srinivasan; Ponnuraja Chinnaiyan (PLoS ONE, 2025)
Background In India, there is no information on health related quality of life (HRQoL) of patients with drug sensitive tuberculosis (TB) using a longitudinal design that includes post- treatment period. This study is the first of its kind in India to assess HRQoL of TB patients from a longitudinal prospective and to identify the factors associated with changes in HRQoL. Methods The study participants were 180 newly diagnosed drug-sensitive smear-positive pulmonary TB patients who were initiated on treatment under the National TB Elimination Programme (NTEP) in Chennai and Tiruvallur districts of Tamil Nadu, South India. The patients were interviewed at four different time points between 2020 and 2023 using validated questionnaires assessing general health (European Quality of Life-5 Dimensions-5 Level (EQ-5D-5L), Short Form health survey (SF-20)), disease specific (St. George's Respiratory Questionnaire (SGRQ)) and mental health including depression and anxiety (Patient Health Questionnaire (PHQ-9), Generalized Anxiety Disorder (GAD-7)). The Friedman test was used to identify changes in HRQoL scores over time and generalised estimating equation (GEE) were applied to identify factors associated with HRQoL. Results HRQoL scores of TB patients, as measured by different scales showed significant improvement from treatment initiation to treatment completion. The GEE analysis showed that the EQ-5D-5L scores over follow-up visits were significantly lower in females (-0.038, p < 0.005) and higher in those who did not skip their main meal in a day (0.077, p < 0.001). The PHQ-9 and GAD-7 scores were significantly higher among females (0.609, p < 0.05; 0.531, p < 0.05). Additionally, PHQ-9 scores were also higher among patients from rural district (0.392, p < 0.05). The SF-20 scores were significantly lower in patients aged >45 years (-1.675, p < 0.05), female (-3.809, p < 0.001) and unemployed (-2.277, p < 0.005). The SGRQ scores were higher in patients aged >45 years (3.043, p < 0.01), females (4.256, p < 0.05) and those from rural district (2.219, p < 0.05). The HRQoL scores were significantly higher in patients who did not skip their main meal and lower in females irrespective of the scales used. Conclusion The HRQoL of TB patients improved significantly over a period of treatment. Gender, age, skipping main meals, region and employment status were the key factors influencing HRQoL. Focusing on HRQoL assessment in the care of TB patients could help to minimize physical, mental and social challenges and enable them to lead a normal life.